Optimal Report Strategies for WBANs Using a Cloud-Assisted IDS. (25th November 2015) - Shen, Shigen; Hu, Keli; Huang, Longjun; Li, Hongjie; Han, Risheng; Cao, Qiying
Abstract : Applying an Intrusion Detection System (IDS) to Wireless Body Area Networks (WBANs) becomes a costly task for body sensors due to their limited resources. To solve this problem, a cloud-assisted IDS framework is proposed. We adopt a new distributed-centralized mode, where IDS agents residing in body sensors will be triggered to launch. All IDS agents are only responsible for reporting the monitored events, not intrusion decision that is processed in the cloud platform. We then employ the signaling game to construct an IDS Report Game (IDSRG) depicting interactions between a body sensor and its opponent. The pure- and mixed-strategy Bayesian Nash Equilibriums (BNEs) of the stage IDSRG are achieved, respectively. As two players interact continually, we develop the stage IDSRG into a dynamic multistage game in which the belief can be updated dynamically. Upon the current belief, the Perfect Bayesian Equilibrium (PBE) of the dynamic multistage IDSRG is attained, which helps the IDS-sensor select the optimal report strategy. We afterward design a PBE-based algorithm to make the IDS-sensor decide when to report the monitored events. Experiments show the effectiveness of the dynamic multistage IDSRG in predicting the type and optimal strategy of a malicious body sensor.